The Origin and Evolution of Magnetic Fabrics in Mafic Sills - Martin, Simon A.; Kavanagh, Janine L.; Biggin, Andrew J.; Utley, James E. P. (Frontiers in Earth Science, 2019)
Studying extinct volcanoes where erosion has exposed dykes and sills provides direct access to the fossil remnants of magma movement, however linking crystallised magma to emplacement dynamics is challenging. This study investigates how magma flow varies across the thickness of a thin (6 metres thick) mafic sill. We use a high-resolution sampling regime to measure micro-scale variations in magnetic anisotropy, which is associated with the orientation of the magnetic particles present within the crystalline rock. Fieldwork was conducted on exposed sills of the British and Irish Palaeogene Igneous Province, Isle of Skye, Scotland. Here Jurassic sedimentary rocks have been intruded by a series of sills, of picrite to crinanite composition, from the Little Minch Sill Complex (c.60 Ma). Anisotropy of magnetic susceptibility (AMS) and anisotropy of anhysteretic remanent magnetisation (AARM) signals have been used to separate a crinanite sill into distinct magnetic groupings. We identified two AMS groups (the upper and lower sill margins, and the central region) and four AARM groups (the lower margin, the middle region, a region just below the upper margin, and the upper margin). Both AMS and AARM signals originate from titanomagnetite of multi-domain or vortex-state to single-domain sized grains, respectively. The AMS and AARM fabrics are aligned with each other in the margin regions preserving a history of magma flow towards the North during initial emplacement. However, in the sill interior the magnetic fabrics are oblique to each other, thus reflecting multiple origins. We suggest the AMS fabrics have recorded magma flow during sill growth, and AARM fabrics have recorded melt percolation flow as the interstitial melt migrated upwards through a solidifying crystal mush. We demonstrate that when AMS and AARM are used in combination they enable a detailed understanding of magma flow and solidification dynamics to be obtained, from initial emplacement to solidification. Overall, our detailed sampling and analysis indicates that magnetic fabrics can be highly variable over small distances, supporting the suggestion of horizontal flow restriction and propagation path migration within growing sills, and that previous reports of magma flow and solidification dynamics based on under-sampled bodies may require reconsideration.